In vivo and in silico Virulence Analysis of Leptospira Species Isolated From Environments and Rodents in Leptospirosis Outbreak Areas in Malaysia - Philip, Noraini; Jani, Jaeyres; Azhari, Nurul Natasya; Sekawi, Zamberi; Neela, Vasantha Kumari (Frontiers in Microbiology, 2021)
The zoonotic disease leptospirosis is caused by pathogenic species of the genus Leptospira. With the advancement of studies in leptospirosis, several new species are being reported. It has always been a query, whether Leptospira species, serovars and strains isolated from different geographical locations contribute to the difference in the disease presentations and severity. In an epidemiological surveillance study performed in Malaysia, we isolated seven novel intermediate and saprophytic species (Lepospira semungkisensis, Leptospira fletcheri, Leptospira langatensis, Leptospira selangorensis, Leptospira jelokensis, Leptospira perdikensis, Leptospira congkakensis) from environments and three pathogenic species from rodents (Leptospira borgpetersenii strain HP364, Leptospira weilii strain SC295, Leptospira interrogans strain HP358) trapped in human leptospirosis outbreak premises. To evaluate the pathogenic potential of these isolates, we performed an in vivo and in silico virulence analysis. Environmental isolates and strain HP364 did not induce any clinical manifestations in hamsters. Strain SC295 caused inactivity and weight loss with histopathological changes in kidneys, however, all hamsters survived until the end of the experiment. Strain HP358 showed a high virulent phenotype as all infected hamsters died or were moribund within seven days post-infection. Lungs, liver and kidneys showed pathological changes with haemorrhage as the main presentation. In silico analysis elucidated the genome size of strain HP358 to be larger than strain HP364 and SC295 and containing virulence genes reported in Leptospira species and high number of specific putative virulence factors. In conclusion, Leptospira interrogans strain HP358 was highly pathogenic with fatal outcome. The constituent of Leptospira genomes may determine the level of disease severity and that needs further investigations.